Living Conditions of the Gond Community in Veerdandi Village of Adilabad District in Telangana - Valya Lunavath (Studies in Social Science & Humanities, 2024)
The Gond community, one of India’s most prominent tribal groups, boasts a rich history and cultural heritage that dates back to the 9th century AD. Their vibrant art, traditional practices, and festivals were renowned, and they once ruled several prominent kingdoms in the hill Gondwana region. However, the British colonial period disrupted their traditional rule, leading to the current socioeconomic profile of Veerdandi village in Telangana’s Adilabad district, revealing significant challenges. Predominantly male (80%), with a large segment in the 25-35 age group (36.7%), the village faces problems such as low literacy rates (55%), lack of education and health facilities, and heavy reliance on agriculture and labour. Modern agricultural technology is limited despite infrastructure such as roads and emergency transport. Demographic and socioeconomic conditions highlight significant challenges in health, education, and living standards. 56.7% of households don’t possess sanitation facilities in their houses and 78.3% are suffering from nutritional deficiency. This underscores the urgent need for government schemes to address the multifaceted problems faced by tribal communities in Telangana. The Pearson Chi-Square value is 18.400. The p-value (.000) was statistically significant in the government support schemes and in preventing tribes’ malnutrition, health issues, and poverty in the study.